Evaluation of Individuals' Mouthwash Buying and Using Habits - Zeliha Güney; Ceyhan C Serdar; Fatma Karacaoğlu; Sivge Kurgan (European Annals of Dental Sciences)

(untitled)
Purpose: Mouthwash use includes processes such as recognizing the problem, collecting information, and evaluating alternatives, and it has been associated with a variety of factors including sociodemographic traits, health, and behavioral aspects. In light of this information, our study aims to evaluate patients' purchase and use habits of mouthwashes.Materials & Methods: 500 patients who applied to Ankara University Faculty of Dentistry Department of Periodontology were included in our study. The patients were asked to fill in a questionnaire consisting of 24 questions about mouthwash usage habits. Data were evaluated with PASW version 20 software. To assess the association between variables, the Chi-square test was performed.Results: 59% of the participants are women, 29.8% consist of individuals between the ages of 18-24, 15.2% of individuals between the ages of 25-34, and 18.3% of individuals between the ages of 35-44. 54.2% of the participants have been using mouthwash for the last 2 years, and 34.5% prefer it because it kills bacteria. This was followed by the answers to prevent gingival diseases, prevent bad breath, and whiten teeth, respectively. The dentist's recommendation is the most important factor affecting the participants when buying mouthwash, but 72% of the participants go to the dentist when needed.Conclusion: Mouthwash usage is related to factors such as the frequency of dental visits and tooth brushing, so all individuals in the community should be educated about mouthwash.Keywords: Oral health, Mouthwash, Preventive dentistry